First La2O2S infrared transparent ceramics. Issue 5 (May 2023) - Le Coz, Alexandre; Durand, Guillaume R.; Cornet, Louis; Herbert, Nathalie; Gouttefangeas, Francis; Joanny, Loïc; Célarié, Fabrice; Cheviré, François; Merdrignac-Conanec, Odile
Abstract: Lanthanum oxysulfide (La2 O2 S) was investigated as infrared transparent ceramic to benefit from stronger chemical bonds and superior mechanical performances to that of non-oxide benchmark infrared materials. La2 O2 S ceramics were processed by hot-pressing powders prepared by combustion synthesis followed by a sulfurization treatment. Powders and ceramics were characterised through various techniques (XRD, UV-Vis-IR spectroscopy, particle size analysis, SEM, Impulse Excitation Technique, microhardness and fracture toughness tests) to assess their purity, study their microstructure and determine their optical and mechanical properties. The study reports the first IR transmission spectra, Poisson's ratio, Young's and shear moduli and fracture toughness values of La2 O2 S polycrystalline ceramics. The ceramics showed transparency in the 2–11 µm range and their mechanical performances were all superior to that of commercial infrared ceramics. The best transmission (89% of the theoretical transmission) was measured at 7.3 µm for 1 mm-thick ceramics hot-pressed at 1200–1250 °C.